Verba Transitif Dialek Melayu Betawi Bekasi pada Situn Bekasi (Puisi dan Pantun) karya Mohammad Guntur Elmogas: Kajian Tagmemik - Rahmat Rahmat (UHAMKA Graduate School Thesis Abstract Collection, 2016)
This study aims to determine the transitive verbs of Malay dialect Betawi Bekasi with the focus of research on transitivity in the study of tagmemik on the book Situn Bekasi; Poetry (Situn) by Mohammad Guntur Elmogas. This research uses qualitative approach with descriptive analysis method. The theory used is Tagmemik's theory pioneered by Kenneth L. Pike. The data obtained from the book review bookSitun Bekasi (Poetry) by Mohammad Guntur Elmogas. Data were analyzed using tagmemic formula based on three levels of grammatical hierarchy, it’s clause analysis, phrase analysis, and word analysis. The analysis is through the selection of preliminary constructions, making work maps, checking work maps, interpretation of data, and formulation of rules, and the writing of formulas based on tagmemic theory. The validity of the data is examined through observational persistence, theoretical understanding, methodological understanding, and consultation. Here are the findings of this study which consists of: 694 transitive clauses, (1) 292 active declarative transitive clauses; (2) 367 passive declarative transitive clauses; (3) 3 active imperative transitive clauses; (4) 9 passive imperative transitive clauses; And (5) 23 passive transitive calories without the offender plus di-. Then, at the phrase level found 27 active declarative transitive verbal phrases, 165 passive declarative transitive verbal phrases, and 10 passive transitional verbal phrases without the prefixes plus the offender.